Pengembangan Media Pembelajaran Flipbook Minuman Campuran Non-Alkohol (Mocktail) pada Mata Kuliah Pengelolaan Bar - Putu Agung Diana Putra Kesiman; Ni Wayan Sukerti; Cokorda Istri Raka Marsiti (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The increasing use of digital technology in higher education has encouraged the development of innovative instructional media that can enhance both theoretical understanding and practical competencies. Feasibility and student acceptance of a flipbook-based learning medium for the Non-Alcoholic Mixed Beverages (Mocktail) topic in the Bar Management course were the focus of evaluation in this study, which was designed to develop such a medium. The study employed a Research and Development (R&D) approach using the 4D model, consisting of the define, design, develop, and disseminate stages. The developed product was evaluated through expert validation involving material, media, and instructional design specialists, followed by a limited trial with undergraduate culinary vocational students. The validation results indicated excellent feasibility, with scores of 90.00% from material experts, 95.00% from media experts, and 95.45% from instructional design experts. Student responses also demonstrated a very positive evaluation, reaching 86.00%. These findings suggest that the flipbook is an effective and appropriate digital learning resource for supporting Bar Management instruction and promoting independent learning.